A blood-based mRNA signature distinguishes people with Long COVID from recovered individuals - Missailidis, Daniel; Ebrahimie, Esmaeil; Dehcheshmeh, Manijeh Mohammadi; Allan, Claire; Sanislav, Oana; Fisher, Paul; Gras, Stephanie; Annesley, Sarah J. (Frontiers in Immunology, 2024)
IntroductionLong COVID is a debilitating condition that lasts for more than three months post-infection by SARS–CoV–2. On average, one in ten individuals infected with SARS CoV- 2 develops Long COVID worldwide. A knowledge gap exists in our understanding of the mechanisms, genetic risk factors, and biomarkers that could be associated with Long COVID.MethodsIn this pilot study we used RNA-Seq to quantify the transcriptomes of peripheral blood mononuclear cells isolated from COVID-recovered individuals, seven with and seven without Long COVID symptoms (age- and sex-matched individuals), on average 6 months after infection.ResultsSeventy genes were identified as significantly up- or down-regulated in Long COVID samples, and the vast majority were downregulated. The most significantly up- or downregulated genes fell into two main categories, either associated with cell survival or with inflammation. This included genes such as ICOS (FDR p = 0.024) and S1PR1 (FDR p = 0.019) that were both up-regulated, indicating that a pro-inflammatory state is sustained in Long COVID PBMCs compared with COVID recovered PBMCs. Functional enrichment analysis identified that immune-related functions were expectedly predominant among the up- or down-regulated genes. The most frequently downregulated genes in significantly altered functional categories were two leukocyte immunoglobulin like receptors LILRB1 (FDR p = 0.005) and LILRB2 (FDR p = 0.027). PCA analysis demonstrated that LILRB1 and LILRB2 expression discriminated all of the Long COVID samples from COVID recovered samples.DiscussionDownregulation of these inhibitory receptors similarly indicates a sustained pro-inflammatory state in Long COVID PBMCs. LILRB1 and LILRB2 should be validated as prospective biomarkers of Long COVID in larger cohorts, over time and against clinically overlapping conditions.